2020
DOI: 10.1007/s10482-020-01430-5
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic characterisation of a novel corynebacterial species pathogenic to animals

Abstract: The genus Corynebacterium includes species of biotechnological, medical and veterinary importance. An atypical C. ulcerans strain, W25, was recently isolated from a case of necrotizing lymphadenitis in a wild boar. In this study, we have analysed the genome sequence of this strain and compared the phenotypic and virulence properties with other corynebacterial pathogens. Phylogenomic analyses revealed that strain W25 belongs to a novel species along with PO100/5 and KL1196. The latter strains were isolated from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…From the genome sequence of C. silvaticum W25, a number of putative virulence factors was annotated [ 23 ]. In this study 12 of these were detected, while 3 were not found ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From the genome sequence of C. silvaticum W25, a number of putative virulence factors was annotated [ 23 ]. In this study 12 of these were detected, while 3 were not found ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is assumed that proteins of this family play a fundamental role in corynebacterial cell surface organization, cell separation, adhesion, and internalization in host cells [ 26 , 58 ]. C. silvaticum strain W25 produced almost all identified virulence factors [ 23 ] already under standard growth conditions except Vsp1, Cpp and NrpS1. The presence of two proteins in the extracellular environment with putative virulence potential (A0A5C5F2T7 and A0A5F0A739) needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genome sequencing and rpoB phylogeny showed that this strain was closer to C. ulcerans and the genome was deposited in GenBank as a strain from this species (accession number CP021417.1). During the submission and review of this manuscript, the description of C. silvaticum was published and suggested PO100/5 as a strain of this species by rpoB phylogeny [4], while a genomic analysis of 28 C. ulcerans strains suggested that PO100/5, W25 and KL1196 could represent a new species [9], although KL1196 had already been classified as C. silvaticum [4].…”
Section: Introductionmentioning
confidence: 99%